Feminism and neo/liberalism: contesting education's possibilities. Issue 2 (4th March 2019) - Blackmore, Jill
ABSTRACT: Feminist theorists critiqued classical liberalism for the gender binaries embedded in social, political and economic theory and everyday social relations. Neoliberalism economises the social and political based on autonomous individualism, equating equity with choice, naturalising the market as the mechanism to allocate social goods and education while disregarding constraining discursive and material contexts. Neoliberalism also co-opts the feminist desire for agency through notions of choice. The paper tracks the historical conditions in Anglophile states that nurtured neoliberalism's uptake with its focus on human capital theory, rethinking the dominant educational discourse of twenty-first-century skills using Yeatman's democratic framing of social liberalism and Nussbaum's capability approach. Feminists argue for a just and civil democratic society that dissolves binary thinking and focuses on relationality, rights and responsibility.